Spectral F Test for detecting TMS/EEG responses. (April 2020) - de Almeida, Alexandre Cardozo; Massote, Mariana Aguiar; Ichinose, Roberto Macoto; Miranda de Sá, Antonio Mauricio Ferreira Leite
Highlights: Our data revealed brain evoked potentials and evoked oscillations after TMS stimuli over the hand motor area of normal subjects. SFT method presents less bias selection than the classic EEG ERD/ERS detection technique. Data from other publications were replicated in our population. The information obtained could be useful to advance the knowledge of motor physiology and diseases. TMS capacitor recharge time must be set-up to avoid undesired neural activation. It is also advisable that the recharge time must also be clearly informed in methods section. Abstract: Electroencephalogram (EEG) is a well-known painless and noninvasive method, measuring the real time brain electrical activity. Transcranial Magnetic Stimulation (TMS) is another noninvasive, painless and safe method, to modulate nerve cells activity. TMS has been increasingly used as a tool in neurosciences. However, its basic mechanisms are not yet fully understood. Simultaneous TMS/EEG recordings are technically challenging, but could provide some more useful information. Eleven normal subjects were submitted to TMS/EEG to investigate its effect on the primary motor cortex area, describing its properties both in time and frequency domains. TMS was also applied to a non-human head model (muskmelon - Cucumis sp.), to evaluate the effect of stimuli artifacts in the electrodes. Time domain techniques revealed the P60, N100, P190 and N280 components. In frequency domain analysis, oscillations between 0.5–70 Hz were observed. After adjusting the TMS capacitor recharge time in order to avoid artifacts during the acquired signal stretch, oscillations were reduced to the 0.5−20 Hz range. Results from other publications were replicated in our population. This information may be useful for motor pathways future studies. TMS capacitors recharge time must be setup to avoid undesired artifacts that could put results in doubt. It is also advisable that the recharge time must also be clearly informed in other works involving TME and EEG.